Polarization of far-IR radiation from p-type germanium under uniaxial pressure and strong electric field - Bondar, V.; Tomchuk, P.; Tulupenko, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Experimental results on the polarization of the far-IR radiation (l=80-120 mm) from p-type germanium under strong uniaxial pressure and heating electric field at liquid-helium temperature arereported. The directions of the polarization and the electric field are shown to be mainly coaxial for samples under pressure and perpendicular to each other for unstrained samples. The possible reasons ofthis phenomenon are discussed.